Problematising Extroversion in South African COVID-19 Lockdown Measures: a case study of women head of families' stories in Khayelitsha on the Cape Flats - Mbombo, Thandazile (African Studies, 2023)
There has been a lack of intersectional gender, race, and class analysis of the present COVID19 pandemic by the government and health organizations in South Africa. This study focuses on a small number of unheard voices of urban poor black women and their experiences of COVID-19 lockdown between 2020 and 2021 on the Cape Flats. Using Khayelitsha as a case study, this research highlights their township-based experiences during COVID-19 lockdown, by exploring the impact on their lives, incomes and health from their perspectives as women head of families. Such voices are often ignored and marginalized in mainstream media. As a small qualitative study, it is based on collecting narratives from a small cohort of female heads of households in Khayelitsha which illustrate that these black women are in general negatively affected economically by top-down western-based imposed COVID-19 lockdown measures (as a form of extroversion). This limited small-scale study points to the need for further research on how these western-imposed methods of managing pandemics and diseases in African realities negate local knowledge of indigenous women and that they are inappropriate and not informed by the everyday lived reality. Lockdown measures in South Africa, therefore, need to be critically reviewed within an African lived reality in future.